2019
DOI: 10.31665/jfb.2019.7200
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of extraction of antioxidants from aromatic herbs and their synergistic effects in a lipid model system

Abstract: Response surface methodology was applied to improve the polyphenol extraction process of rosemary, oregano, sage, and thyme. Aqueous ethanol (EtOH 50%) rendered the highest polyphenol extraction yield for all tested samples. Based on their total phenolic contents, rosemary, oregano, and thyme were selected for evaluation of their scavenging activities towards DPPH radical and ABTS radical cation and application in an oil model system. All extracts decreased the production of primary oxidation compounds  during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The extraction at the central point (or centroid) represents an equal contribution of all three solvents (0.333, 0.333, 0.333). Runs 7–9, representing the extraction in three replicates, allow estimating the variation in the responses at the central point and provides a basis for the lack-of-fit test [ 78 , 79 ]. The response function was the TPC, which was evaluated in two different advanced breeding lines.…”
Section: Methodsmentioning
confidence: 99%
“…The extraction at the central point (or centroid) represents an equal contribution of all three solvents (0.333, 0.333, 0.333). Runs 7–9, representing the extraction in three replicates, allow estimating the variation in the responses at the central point and provides a basis for the lack-of-fit test [ 78 , 79 ]. The response function was the TPC, which was evaluated in two different advanced breeding lines.…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between the EI value and the applied temperature of extraction is shown in Figure 2. The data indicated that to obtain the maximum content of electroactive compounds of oregano extract, the optimal temperature of the extraction procedure was 85 • C. According to the literature data, the efficiency of polyphenol extraction is better at lower temperatures [15,16]. It should be emphasized that electrochemical measurements do not allow polyphenols to be distinguished from other compounds with antioxidant activity that are likely to be better extracted at higher temperatures.…”
Section: Electrochemical Activity Of Oregano Extractmentioning
confidence: 99%
“…A detailed calculation of the effect of extraction temperature and used environment on the phytochemical and bioactive properties of Ocimum gratissimum extracts was presented in the study by Onyebuchi and Kavaz [15]. It is well known that, apart from temperature, other factors, including mainly the used extractants, have a significant impact on the extraction efficiency, as described by Vieira et al [16]. The data indicated that to obtain the maximum content of electroactive compounds of oregano extract, the optimal temperature of the extraction procedure was 85 °C.…”
Section: Electrochemical Activity Of Oregano Extractmentioning
confidence: 99%
“…However, oxidation of polyunsaturated fatty acids, still occurs, even under the strict packaging practices, and the safety of synthetic antioxidants, such as butylated hydroxyanisole and butylated hydroxytoluene (BHT), is questionable because the scientific evidence suggests that there are carcinogenic and toxic effects in animal models overexposed in terms of the concentration and duration of exposure to such compounds. [9][10][11] The recent literature has extensively encouraged the safe employment in food preparations of natural additives from a number of vegetable sources 12 or, even better, from byproducts generated during the processing of plant-based food. 13 In this respect, approximately 13.7 million metric tons of hulls and over 0.74 million metric tons of skins are churned out every year from the global peanut processing industry, most of which are treated as waste, and, hence are dumped into the environment or burned.…”
Section: Introductionmentioning
confidence: 99%
“…At the industrial level, the retardation of lipid oxidation is therefore mandatory to obtain high‐quality peanut products, and is usually performed by nitrogen‐filled headspaces, vacuum packaging, light barriers or antioxidant addition. However, oxidation of polyunsaturated fatty acids, still occurs, even under the strict packaging practices, and the safety of synthetic antioxidants, such as butylated hydroxyanisole and butylated hydroxytoluene (BHT), is questionable because the scientific evidence suggests that there are carcinogenic and toxic effects in animal models over‐exposed in terms of the concentration and duration of exposure to such compounds 9–11 …”
Section: Introductionmentioning
confidence: 99%